Prospects of Ecotourism in Bandipur - Sigdel, Tej Prasad (The Third Pole: Journal of Geography Education, 2014)
Ecotourism denotes ecological or environment friendly tourism. This study is confined to Bandipur area, a popular tourist destination in Tanahun district. Bandipur has a great prospect of ecotourism owing to natural beauty, scenic attraction and cultural diversity. It is rich in natural paradise and socio-cultural diversities. Accessibility, pleasant Climate, richness of natural beauty, suitable place for view point, high stock of biodiversity and native culture of simple and friendly people make Bandipur unique ecotourism destination. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11555 The Third Pole Vol. 11-12, 2012 Page : 50-55